Ball Impact Response of Unstrengthened and Chemically Strengthened Glass Bars. Issue 1 (7th December 2013) - Jannotti, Phillip; Subhash, Ghatu; Varshneya, Arun K.; Rouxel, T.
<x xml:space="preserve">Abstract</x> Ball impact experiments were conducted at impact velocities of 52–345 m/s on unstrengthened and chemically strengthened lithium aluminosilicate glass bars to assess the damage propagation characteristics. The damage was captured by high‐speed imaging at frame rates up to 500 000 frames per second (fps). Upon impact, the damage front in the unstrengthened glass reached a maximum velocity of 1626–2135 m/s, and rapidly fell to zero within a short distance. On the contrary, the damage front in the strengthened glass reached an initial velocity of 1791–2275 m/s, but then stabilized to a constant velocity of 1920 m/s until the entire glass bar was consumed. In addition, the cascading release of stored energy due to strengthening led to self‐sustained damage propagation preferentially within the outer layers of the glass bar (predominantly within the compressive zones) at a higher rate than in the interior region (dominated by residual tension). This is counter to what has been traditionally reported in the literature. Stress wave reflection from the rear of the unstrengthened bar caused tensile cracking (i.e., spallation), but the ultrahigh residual compression in the strengthened bar prevented similar damage initiation. Finally, it is suggested that strengthened glasses are most suitable as intermediate layers in laminate window panels for impact applications.